Development,Running Mode and Key Technologies Analysis of Regional Cargo Drones - XU Jianhua; LI Quan (Hangkong gongcheng jinzhan, 2022)
Regional cargo drones provide a more economical and efficient transportation mode for freight in remote areas,mountains,plateaus,islands and cities,and play an important role in emergency rescue and supplies at wartimes.In this paper the development of regional cargo drones is reviewed,the competitive advantages between regional cargo drones,human aircraft,and land traffics are compared,and the relatively safe running mode of cargo drones under the current technical status is discussed,which is“the pipeline flight of point to point”.Finally,key technologies of regional cargo drones are analyzed,including the technology of airworthiness,aircraft platforms,datalink,navigation and autonomous take-off and landing technology and so on.The application of regional cargo drones need to carry out systematic construction,pay close attention to operational risk,laws and regulations for UAVs,airspace management,flight management,airport facilities and other construction work,in addition of aircraft platforms.